ADMINISTRATIVE REFORMS OF THE FIRST HALF OF ХІХ OF CENTURY IN SCIENTIFIC RESEARCHES OF UKRAINIAN SCIENTISTS (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Administrative reforms of the first half of the 19th century in the scientific research of Ukrainian scientists are important studies for the development of economic theory on the territory of Ukraine. After all, one of the many possible ways of creating the history of Ukrainian management thought is a thorough study of the theoretical and practical contribution of outstanding scientists and personalities to the business of reforming management.Purpose: to reveal the main trends in the formation of management opinion in Ukraine using the example of the analysis of management reforms and scientific works of Ukrainian scientists. To determine the main trends in the formation of management opinion in Ukraine in the first half of the 19th century.Methods. The following methods were used in the course of this research: information collection, applied research (aimed at obtaining and using the data obtained for practical purposes in the study of the discipline “Economic Theory (micro- and macroeconomics), generalization and comparison, analysis (substantiation of reform projects in the field of economy, finance, legislation, by prominent Ukrainian scientists and statesmen of the nineteenth century).Results. This research article summarizes methodological approaches to management reforms in the research of Ukrainian scientists. They are analyzed from the standpoint of substantiation of reform projects in the field of economics, finance, and legislation by prominent Ukrainian scientists and statesmen: V. N. Karazin (1773-1842), M. H. Bunge (1823-1895), M. A. Baludiansky (1769-1847), T. F. Stepanov (1795-1847), D. P. Zhuravsky (1810-1856), and others.Conclusions. Particular attention is paid to the views of scientists and the role of the state in the economy and reforms. Thus, in the first half of the 19th century, domestic scholars took an active part in the development of management issues. However, as in the world thought, these developments did not form an independent branch of knowledge, which later became known as management. This research summarizes the main provisions of the scientific views of the leading representatives of Ukrainian management thought of the first half of the 19th century.
Keywords: administrative idea, reforms, history of the Ukrainian administrative idea, turnover, state administration, public finances, financial reforms.